Evaluation of safety standards in operating rooms of Tehran University of Medical Sciences (TUMS) Hospitals in 2010 - SMH Mousavi; H Dargahi; M Hasibi; Z Mokhtari; G Shaham (Tehran University of Medical Sciences, 2011)
Background and Aim: The operating room is one of the main units in a hospital, where the most important phase of treatment is performed. Due to the physical properties, use of gases, and different electric devices in the operating room, the safety of both the patients and the staff should be considered carefully. This study aims to estimate the safety standards of the operating rooms in ‎Tehran University Hospitals and to provide solutions to the existing problems. Materials and Methods: This is a descriptive, cross-sectional study conducted in the operating rooms of TUMS hospitals. The research instrument was a checklist used by interviewers while observing the place. The safety standards were studied in terms of physical environment, protection against fire‎, personnel safety, patients' safety, and infection control. The data were analyzed by SPSS software. Results: The overall safety of the operating rooms of TUMS hospitals was found to be 84.9 percent. The figures for infection control and personnel safety, however, were lower. Conclusion: The operating rooms of Tehran University of Medical Sciences hospitals were studied in terms of five safety standards. Considering the physical environment, fire protection, and patient safety, they were quite safe but as to infection control they were relatively safe. However, they were found to be unsafe regarding the safety of their staff. Tehran Heart Center with an overall safety of 97.5% for its operating rooms can be considered as a model for the other TUMS treatment centers.